Analisis Kepuasan Pelayanan Penggunaan Mobile Banking BCA - Zahrotul Hayat; Syamsul Hidayat (Lembaga Pengembangan Kinerja Dosen, 2024)
Technological developments have made the mobility of people's activities more practical in meeting their financial needs. Only using a smartphone and internet network, customers can carry out banking transactions anywhere and anytime. This research discusses the development of economic digitalization in the banking sector, namely Mobile Banking technology innovation at BCA Bank. Therefore, this research aims to analyze the level of service satisfaction using BCA Mobile Banking (BCA Mobile). The research method used by researchers is qualitative and descriptive analysis techniques, as well as a data collection system using questionnaires. The data obtained was taken from the results of distributing questionnaires in the Bina Bangsa University Management Study Program which used BCA Mobile and a sample of 110 respondents was obtained. The results of the research show that BCA Mobile is very helpful in carrying out banking activities and the existing services have a significant influence on user satisfaction at Bina Bangsa University Management Study Program